RANK receptor oligomerisation in the regulation of NFκB signalling - Das, S (Bioscientifica Ltd, 2014)
The interaction of receptor activator of NFκB (RANK), a member of the tumour necrosis factor receptor superfamily, with RANK ligand is crucial for the formation, function and survival of osteoclasts. The role of the cytoplasmic oligomerisation domain (pre-ligand assembly domain; PLAD or ‘IVVY’ motif) in the ligand-dependent activation of downstream NFκB signalling has not been studied previously. The discovery of truncating mutations of TNFRSF11A (W434X and G280X that lack the PLAD) as the cause of rare cases of osteoclast-poor osteopetrosis offered the opportunity for functional study of this region. Recapitulating the W434X mutation by transcription activator-like effector nuclease (TALEN)-mediated targeted disruption of Tnfrsf11a within the region homologous to W434X in the mouse macrophage-like cell line RAW264.7 impaired formation of osteoclast-like cells. Using overexpression studies, we demonstrated that, in contrast to WT-RANK, the absence of the PLAD in G280X-RANK and W434X-RANK prevented ligand-independent but not ligand-dependent oligomerisation. Cells expressing W434X-RANK, in which only two of the three TRAF6-binding motifs are present, continued to exhibit ligand-dependent NFκB signalling. Hence, the absence of the PLAD did not prevent ligand-induced trimerisation and subsequent NFκB activation of RANK, demonstrating that therapeutic targeting of the PLAD in the prevention of osteoporosis may not be as effective as proposed previously.